2017
DOI: 10.1111/jog.13219
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance and predicting indicators of post‐cancer‐treatment survival in terminally ill patients with ovarian cancer

Abstract: Half of the patients received chemotherapy within 75 days of death and we did not identify any survival benefit in patients who received chemotherapy near the end of life. We should provide information to patients about their prognosis and discuss the timing of withdrawal from chemotherapy from the early stage of their recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…These studies were published between 1999 and 2023. Six studies were conducted in China [ 26 , 27 , 30 32 , 35 ], four in Japan [ 21 , 24 , 29 , 34 ], and one each in Austria [ 22 ], Australia [ 23 ], Poland [ 25 ], the USA [ 28 ], and Turkey [ 33 ]. Each of the included studies was retrospective in design and published in English [ 21 35 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These studies were published between 1999 and 2023. Six studies were conducted in China [ 26 , 27 , 30 32 , 35 ], four in Japan [ 21 , 24 , 29 , 34 ], and one each in Austria [ 22 ], Australia [ 23 ], Poland [ 25 ], the USA [ 28 ], and Turkey [ 33 ]. Each of the included studies was retrospective in design and published in English [ 21 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…Thirteen studies were single-center investigations [ 21 , 23 25 , 27 35 ], and two were multicenter trials [ 22 , 26 ]. Eleven studies included patients with OC with FIGO stages I–IV [ 21 , 22 , 24 27 , 30 , 32 35 ], three included those with FIGO stages III–IV [ 23 , 28 , 31 ], and one included OC stage IV [ 29 ]. In addition, the threshold CRP level was 3.5–70 mg/L (median, 10 mg/L).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is partially in concordance with our results as we also found increased white blood cell count and CA125 in patients with malignant tumors. Utsumi et al 10 reviewed 77 charts of terminally ill patients with ovarian cancer and concluded that poorer performance status, elevated white blood cell count and higher CRP value significantly correlated with shorter survival. This is partially in concordance with the results of our study, which revealed significant correlation of higher CRP and shorter overall survival.…”
Section: Discussionmentioning
confidence: 99%
“…There is some contradicting evidence to suggest that chemotherapy has a role in palliation of symptoms with an apparent improvement in quality of life 37 as well as recent reports of lack of survival benefit of patients who are treated with empirically chosen chemotherapy within 3 months from their end of life. 38 When ovarian cancer progresses, goals change from cure to prolongation of life with the best possible quality for the patient. Goals of palliative chemotherapy for cancer after fourth line are mainly directed at controlling symptoms, preventing secondary burdens of toxicities, providing ease of access, limiting impact on patients' quality of time, avoid hospitalizations as far as possible, reducing economic burden of testing, and permitting access to testing at point of service.…”
Section: Discussionmentioning
confidence: 99%